STUDENTS' CHALLENGES DURING ONLINE LEARNING IN ENGLISH CORRESPONDENCE SUBJECT - Arahman, Sabrina; Riza, Armilia; Afriyanti, Rika (LINGUA LITERA : journal of english linguistics and literature, 2025)
This study investigates the challenges faced by English Education students from the 2021 cohort at Universitas PGRI Sumatera Barat during online learning in the English Correspondence subject. The purpose of this research is to identify the specific challenges encountered by students who underwent six months of online instruction using the Zoom and e-learning platforms. Employing a qualitative research method with a phenomenological approach, the study collected data through interviews to gain insight into the students' lived experiences. The research sample comprised nine students from the 2021 cohort, selected via purposive sampling based on their simultaneous participation in both practice teaching and online lectures for the English Correspondence course. The findings reveal that the primary challenges students faced were unstable and slow internet connections, which led to technical disruptions, as well as a significant lack of self-discipline. This study concludes that these challenges, both technical and non-technical, critically impact the effectiveness of online learning and must be addressed to enhance the student experience.